1992
DOI: 10.2337/diacare.15.8.976
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) in Diabetic Patients with and Without Chronic Renal Failure

Abstract: Lp(a) may contribute to the increased prevalence of atherosclerotic disease in diabetic patients and patients with chronic renal failure, especially in IDDM patients whose lipoprotein pattern was not different from that of the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
2
20
1
1
Order By: Relevance
“…Conclusions as to the effect of improved glycemic control on Lp(a) levels have also varied [29,33,[35][36][37][38][39][40][41][42]. At follow-up in the DCCT, Caucasian subjects who received conventional treatment had significantly higher levels of Lp(a) than both the subjects who received intensive treatment and those in a nondiabetic control population.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…Conclusions as to the effect of improved glycemic control on Lp(a) levels have also varied [29,33,[35][36][37][38][39][40][41][42]. At follow-up in the DCCT, Caucasian subjects who received conventional treatment had significantly higher levels of Lp(a) than both the subjects who received intensive treatment and those in a nondiabetic control population.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Some investigators found elevated Lp(a) levels in subjects with IDDM compared with normoglycemic control subjects [29,30], white others have not [31][32][33][34]. Several studies of IDDM subjects have shown that Lp(a) levels increase with worsening glycemic control [35][36][37][38][39][40], although other studies have not [29,33,41,42]. Finally, earlier studies showed a direct correlation between the degree of proteinuria and increasing Lp(a) levels in subjects with IDDM [43][44][45][46], but more recent studies have not [31,42,47].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estes dados estão de acordo com o que já foi descrito na literatura em outros estudos transversais (44)(45)(46). A maioria dos estudos que descreve uma associação, esta é principalmente com os níveis de colesterol total e LDL-colesterol (47,48) e ainda é importante ressaltar que na maioria dos estudos clínicos, onde há alterações significativas do perfil lipídico nos pacientes diabéticos tipo 1, estes apresentam uma taxa de excreção de albumina já considerada como macroalbuminúria (28).…”
Section: Microalbuminúria Em Pacientes Com Dm1unclassified